2018
DOI: 10.1097/ee9.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Concentrations of Per- and Polyfluoroalkyl Substances and Breastfeeding Duration in the Norwegian Mother and Child Cohort

Abstract: Background Per- and polyfluoroalkyl substances (PFASs) have been widely produced, many of them persist in the environment, and have been associated with various health effects. Previous studies have identified inverse associations between perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS) and breastfeeding duration, but have been limited in investigation of other PFASs. Methods We measured the associations between plasma concentrations of 9 different PFASs and cessation of breastfeeding before 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…The included studies were published between 2010 and 2022, and were based on data from women giving birth between 1996 and 2012 (Table 3). Five of the studies focused on women living in northern Europe [40][41][42][43][44] and one was from women in the United States [45]. The study size ranged from 336 [45] to 2374 participants [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were published between 2010 and 2022, and were based on data from women giving birth between 1996 and 2012 (Table 3). Five of the studies focused on women living in northern Europe [40][41][42][43][44] and one was from women in the United States [45]. The study size ranged from 336 [45] to 2374 participants [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The study size ranged from 336 [45] to 2374 participants [41]. Five studies were prospective cohort studies [40,[42][43][44][45], and one was based on data from a natural experiment, in which contaminated drinking water caused serum PFHxS, PFOS, and PFOA concentrations to be 135, 35, and 5 times higher, respectively, in one Swedish municipality, Ronneby, compared to a nearby municipality [41]. The median duration of total breastfeeding ranged from 6 [45] to 9 months [44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These persistent industrial chemical wastes are toxic to living beings. Human and animal studies of PFAS revealed that these substances could lead to neurological, liver, and lung problems and disrupt hormonal balance. Additionally, the cancerous effect of PFAS was investigated, and results indicate that PFAS exposure increases the risk of getting kidney and testicular cancer. , Epidemiological studies have also shown that exposure to specific PFAS has several health effects: immunosuppression among children, adolescents, and adults as well as other targeted organs such as the placenta in pregnant women; there is also sufficient proven evidence indicating that PFAS exposure would affect breast milk production and breastfeeding duration. There are also findings linking PFAS with elevated cholesterol levels and significant birth defects. , …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PFASs begins in-utero, where they readily cross the placental barrier [8]. Exposure can continue early in life with PFASs able to enter breast milk [8]; indeed, population studies have suggested that breastfeeding duration and milk quantity are adversely altered by PFASs exposure [9]. Exposure levels disproportionately affect children, with PFAS concentrations in young children generally exceeding maternal serum concentrations, which can lead to adverse effects such as obesity, hormone suppression, and thyroid diseases in childhood and over the lifespan [2].…”
Section: Introductionmentioning
confidence: 99%